Posttraumatic Fat Embolism and Medicolegal Evaluation a Case Report - Meral, Orhan; Erdoğan, Nihal; Güler, Hülya; Kaya, Ahsen; Koçak, Aytaç (The Bulletin of Legal Medicine, 2014)
Fat embolism is defined as the presence of fat globules in the lung parenchyma or circulation after long bone fracture or other major trauma and often asymptomatic. However, fat embolism syndrome is the clinical symptoms and signs that defined after fat embolism and can be a fatal statement. It often manifests 24 - 72 hours after trauma with central nervous system, respiratory and urinary tract, eyes and skin symptoms. Early diagnosis and treatment is important to reduce the risk of death. While these cases often carry judicial nature and so, this clinical situation must be kept in mind during the arrangement of the forensic reports of these cases. In this case report, a 30-year-old male case is detailed in which the patient was injured after an extravehicular traffic accident and developed pulmonary fat embolism afterwards and was presented to our department with the request of a final forensic report. It is intended to emphasize on the elements to take into consideration while diagnosing fat embolism and draw attention to the changes made under subject "injuries result with risk of life", in the guide published in June, 2013 with title "The Evaluation of Injury Crimes Defined in the Turkish Penal Code with regards to Forensic Medicine". Keywords: Forensic report, complication, fat embolism, medicolegal evaluation.